Victimes d’actes criminels : une intervention professionnelle - Engel, Frema (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1990)
Victims of crime suffer tremendous psychological damage as a result of the trauma that they experience. The effects can be totally debilitating and can destroy their lives. The author discusses the reactions, symptoms of acute stress and stages of recovery of crime victims. She also discusses post-traumatic stress syndrome (PTSD), and the kind of help victims need to recover from their injuries. Finally, she suggests how mental health professionals in particular and society in general could better respond to crime victims.